Sclerostin Antibody Treatment Improves the Bone Phenotype of Crtap–/– Mice, a Model of Recessive Osteogenesis Imperfecta. (12th February 2016) - Grafe, Ingo; Alexander, Stefanie; Yang, Tao; Lietman, Caressa; Homan, Erica P; Munivez, Elda; Chen, Yuqing; Jiang, Ming Ming; Bertin, Terry; Dawson, Brian; Asuncion, Franklin; Ke, Hua Zhu; et al.
ABSTRACT: Osteogenesis imperfecta (OI) is characterized by low bone mass, poor bone quality, and fractures. Standard treatment for OI patients is limited to bisphosphonates, which only incompletely correct the bone phenotype, and seem to be less effective in adults. Sclerostin‐neutralizing antibodies (Scl‐Ab) have been shown to be beneficial in animal models of osteoporosis, and dominant OI resulting from mutations in the genes encoding type I collagen. However, Scl‐Ab treatment has not been studied in models of recessive OI. Cartilage‐associated protein (CRTAP) is involved in posttranslational type I collagen modification, and its loss of function results in recessive OI. In this study, we treated 1‐week‐old and 6‐week‐old Crtap –/– mice with Scl‐Ab for 6 weeks (25 mg/kg, s.c., twice per week), to determine the effects on the bone phenotype in models of "pediatric" and "young adult" recessive OI. Vehicle‐treated Crtap –/– and wild‐type (WT) mice served as controls. Compared with control Crtap –/– mice, micro–computed tomography (μCT) analyses showed significant increases in bone volume and improved trabecular microarchitecture in Scl‐Ab–treated Crtap –/– mice in both age cohorts, in both vertebrae and femurs. Additionally, Scl‐Ab improved femoral cortical parameters in both age cohorts. Biomechanical testing showed that Scl‐Ab improved parameters of whole‐bone strength in Crtap –/– mice, with more robust effects in the week 6 to 12 cohort, but did not affect the increased bone brittleness. Additionally, Scl‐Ab normalized the increased osteoclast numbers, stimulated bone formation rate (week 6 to 12 cohort only), but did not affect osteocyte density. Overall, our findings suggest that Scl‐Ab treatment may be beneficial in the treatment of recessive OI caused by defects in collagen posttranslational modification. © 2015 American Society for Bone and Mineral Research.